Chitosan-based adsorption and freeze deproteinization: Improved extraction and purification of synthetic colorants from protein-rich food samples. (1st December 2015) - Kong, Cong; Fodjo, Essy Kouadio; Li, Dan; Cai, Youqiong; Huang, Dongmei; Wang, Yuan; Shen, Xiaosheng
Highlights: Mixture of ammonia, ethanol and water showed highest performance in extraction. Freeze deproteinization avoids the colorants loss. Pre-cleaning of the extract was explored by chitosan as sorbent. Improved performance obtained on the determination of 8 synthetic colorants in protein-rich samples. Abstract: A freeze method for deproteinization coupling with the chitosan purification process was developed for the determination of 8 synthetic food colorants in protein-rich samples. The solvents for extraction and different methods for deproteinization were examined and selected. Chitosan was employed for the purification after deproteinization, and further compared with the traditional polyamine purification method. Determination of the purified extract was conducted through the separation using high performance liquid chromatography and detection by multi-wavelength mode. Under the optimum conditions, the method showed good linearity between 0.6 and 10 mg/kg, for the 8 synthetic colorants, and the limit of detection was between 0.1 and 0.4 mg/kg as was defined when the ratio of signal to noise was three. The recoveries of the spiked samples were found to be between 83% and 91%. The intra-day precision and inter-day precision was estimated to be 3–10% and 6–12%, respectively. The developed method could be applied to deproteinization and clean-up for pretreatment of protein-rich samples.